Post-Traumatic Stress Disorder, Depression, and Binge Drinking in the Reserve Component of the U.S. Armed Forces. Issue 10 (1st October 2016) - Ursano, Robert J.; Wang, Jing; Ramsawh, Holly; Russell, Dale; Benfer, Natasha; Gifford, Robert K.; Cohen, Gregory H.; Galea, Sandro; Fullerton, Carol S.
ABSTRACT: Objectives: We documented the prevalence of post-traumatic stress disorder (PTSD), depression, and binge drinking in U.S. Reserve and National Guard (Reserve Component [RC]) personnel for each service and branch by rank, gender, and deployment status. Methods: Structured interviews were conducted with a nationally representative sample of RC personnel ( n = 2, 003). We used weighted descriptive statistics to examine the prevalence of PTSD, depression, and binge drinking. Results: The prevalence of PTSD was 6.7%, depression was 6.8%, and binge drinking was 11.5%. The prevalence of having one or more mental health problems investigated in this study was 19.8%. The prevalence of binge drinking was higher for enlisted men (14.8%) than enlisted women (2.6%). Having one or more mental health problems was nearly twice as high for enlisted men (23.4%) vs. enlisted women (12.9%). For deployed personnel, the prevalence of PTSD or having one or more mental health problems was approximately twice that of never-deployed personnel. Conclusions: Prevalence of mental health problems can inform prevention and treatment for RC personnel. Further research is needed to identify risk factors for PTSD, depression, and binge drinking. Interventions for RC personnel should consider service and branch, rank, gender, and deployment status.